Analisis Gaya Hidup Seseorang atas Iklan dan Kepercayaan terhadap Keputusan Pembelian Fitur Spaylater pada Aplikasi Shopee - Adinda Azmi Dwi Putri; Septia Sari Ardani; Marsandra Clarisa; Fitri Ayu Nofirda (Politeknik Bisnis Indonesia, 2023)
This research discusses the impact of lifestyle, advertising and trust on purchasing decisions for the Spaylater feature on the Shopee application. The development of digital technology has changed consumer mindsets and habits, influencing purchasing decisions. Psychological factors and personal characteristics of consumers play an important role in purchasing decisions, with advertising also influencing purchasing decisions using Spaylater. Trust in Spaylater is also a crucial factor in influencing purchasing decisions. The research method uses variables X lifestyle, advertising, and trust, with variable Y purchasing decisions. The research results show that advertising and trust have a positive and relevant influence on purchasing decisions, while lifestyle has no relevant influence. From the test results, it was concluded that advertising and trust have the greatest influence on consumer decisions in using the Spaylater feature on the Shopee application.